Teaching in Lao PDR - Benveniste, Luis; Marshall, Jeffery; Santibañez, Lucrecia (Washington, DC: World Bank, 2012)
Educational attainment and literacy rates in Lao PDR have improved significantly. Years of education research have established that, after family background, teachers are one of the most important determinants of student outcomes. A good teacher can have a long lasting impact on what and how much a student learns. The importance of teachers is even more significant in developing countries where, on average, parental socioeconomic status tends to be low and notable resource constraints abound. In these circumstances, good teaching becomes all the more critical as parents might not be able to provide academic help at home or school resources may not be readily available to enrich the classroom environment To begin to understand how these challenges manifest themselves in Lao PDR, this study examines the current status of teachers in primary and lower secondary schooling as well as government policies that strive to improve teaching in particular and education quality more generally. It explores teacher supply, and demand to identify potential bottlenecks in the availability of trained personnel. It describes teachers demographic characteristics and their skills. It looks at teacher salaries, their level and how this compares to other countries. It examines classroom conditions, pupil-teacher ratios, educational expenditures, and other factors that influence the context of teaching and opportunities to engage in high quality instructional practice. Lastly, this report explores teacher performance, as measured by teacher attendance, teaching practices, and student assessment outcomes. In addition, the report draws on a recent body of research that has explored various aspects of teachers and teaching in Lao PDR. The discussion focuses on primary and lower secondary school teachers, who together represent 87 percent of the teacher population in Lao PDR. Throughout the paper, effort is made to investigate how teachers and their teaching situation vary by region of the country (uplands, mountain, and lowlands) and type of school (urban, rural, and remote). It also explores variations by gender and ethnicity.